Evaluation of the Factors Affecting the Preferences and Perceptions of Consumers Toward Local Dairy Products in Palestine - Samer Mudalal; Ola Anabtawi; Alma Irshaid; Jihad Abdallah (Journal of Agriculture and Environment for International Development)
Local foods have a positive environmental impact. Local foods not only reduce energy consumption and, consequently, the carbon footprint of the supply chain, but also require less additional packaging from producers to protect food products during transportation and marketing. This study aims to evaluate consumers’ preferences and perceptions towards local dairy products in Palestine. 799 participants were surveyed and segmented based on their purchasing behavior, perceptions, and willingness to buy local dairy products. The study revealed that consumers are more inclined to purchase local dairy products compared to imported dairy products, the main competitors. Consumers showed higher intentions to buy Nabulsi cheese and Labneh compared to other dairy products, with significant positive correlations between product attributes. Based on Principal Components Analysis (PCA), three components were extracted from 18 variables. The three components identified are (1) PCA1: product attributes; (2) PCA2: perception of local products; and (3) PCA3: willingness to purchase local dairy products. These components explained 38.73%, 26.10%, and 5.71% of the total variation, respectively. Cluster analysis grouped consumers into two clusters with marked differences in socio-demographic structure and in certain perceptions of local dairy products compared to their imported counterparts. In conclusion, despite that satisfaction in the quality characteristics of local products was not very high, respondents still expressed a strong desire to buy local dairy products.